2019
DOI: 10.1093/schbul/sby119
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations in Children and Adolescents: An Updated Review and Practical Recommendations for Clinicians

Abstract: Hallucinations in children and adolescents are now known to occur on a continuum from healthy to psychopathology-related phenomena. Although hallucinations in young populations are mostly transient, they can cause substantial distress. Despite hallucinations being widely investigated, research so far has had limited implications for clinical practice. The present article has 3 main aims: (1) to review research findings since 2014 (when the last major review of the area was published); (2) to present assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 103 publications
1
49
0
Order By: Relevance
“…Hallucinations are frequently observed in children and adolescents in both clinical and nonclinical contexts. 36 , 37 A phenomenological analysis of the hallucinations reported in the National Institute of Mental Health (NIMH) childhood-onset schizophrenia cohort revealed that the number of sensory modalities involved may serve as an indicator of the neurodevelopmental weight of the disorder. 26 This idea of MMHs as a proxy of developmental vulnerability was also confirmed in a case series showing that the number of sensory modalities involved in early-onset hallucinations was related to the probability that a given child ever experienced prior traumatic events.…”
Section: Prevalencementioning
confidence: 99%
“…Hallucinations are frequently observed in children and adolescents in both clinical and nonclinical contexts. 36 , 37 A phenomenological analysis of the hallucinations reported in the National Institute of Mental Health (NIMH) childhood-onset schizophrenia cohort revealed that the number of sensory modalities involved may serve as an indicator of the neurodevelopmental weight of the disorder. 26 This idea of MMHs as a proxy of developmental vulnerability was also confirmed in a case series showing that the number of sensory modalities involved in early-onset hallucinations was related to the probability that a given child ever experienced prior traumatic events.…”
Section: Prevalencementioning
confidence: 99%
“…Although AVH are relatively common among adolescents in the general population (prevalence ranging from 7.3% to 12.4%) [4-6], 34% of adolescents with AVH and psychopathology have had at least one suicide attempt compared to 13% of adolescents without AVH [7]. This emphasizes the need to further investigate AVH in youth to better identify individuals with need for care and learn more about the underlying mechanisms causing this phenomenon [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the first article, Maijer et al 4 present a summary of the issues that have dominated the field on hallucinatory experiences in children and adolescents since the last 2014 ICHR review on the topic. 5 Notably, the study warns us to be careful about an overreliance on the significance of terminology such as “persistence” given the varied trajectories of symptoms across psychotic, affective, anxiety, autistic and personality disorders, and the behavioral and functioning spectrum.…”
mentioning
confidence: 99%